(untitled) (Docentes 2.0 Journal, 2021)
This essay demanded an interpretive analysis derived from the Computer Law chair taught by its author in the tuition of the Law career inserted in the professional axis of the Autonomous Regional University of the Andes, Ibarra extension of Ecuador. Its purpose was to support the scenario that contains the behavior of antisocials who use electronic, telematic, or computational means on purpose the so-called digital age due to the ubiquity of the connected world based on a dual syndemic factor that now represents more than the pandemic outbreak, the overwhelming opportunism of the so-called clans of the network due to the interactions that overflow and exacerbate the prognosis and criminal burden in the violation of the legal right protected by the laws not only local but also on the international board, such as the security of the assets of the information and communication systems as a response to the problem situation that is expanding at a dizzying speed from a didactic perspective immersed in the students. The reflection that combined the legal-pedagogical domain allowed enriching and strengthening with positions explicitly evaluated by opinions expressed made known about the real instructional administration of computer law as a subgeneric branch of legal sciences with emphasis on criminal matters.